Plasmacytoma of the Nasolacrimal Duct Simulating Dacryocystitis: An Uncommon Presentation for Extramedullary Relapse of Multiple Myeloma - Kalayoglu-Besisik, Sevgi (S. Karger AG, 2012)
The most common site for localized forms of plasma cell neoplasms (extramedullary plasmacytoma; EMP) is the upper respiratory tract, including the oropharynx, nasal cavities, sinuses and larynx. A 50-year-old woman with a history of myeloma in complete remission after autologous stem cell transplantation complained of two weeks of epiphora of the left eye with subsequent diplopia, bloody nasal discharge and progressive swelling around the nasolacrimal sac. A solitary mass in the left sinonasal area, extending to the nasolacrimal duct (NLD) was detected on MRI, whose histopathological examination was consistent with plasmacytoma. Further clinical investigation ruled out multiple myeloma (MM). The patient underwent debulking surgery and adjuvant chemotherapy followed by local radiotherapy in an attempt to achieve complete response. Despite being a rare entity, EMP of the NLD should be considered in the differential diagnosis of epiphora and dacryocystitis. To our knowledge, this is the first case of a plasmacytoma of the NLD presenting as isolated extramedullary relapse of MM. The follow-up in EMPs should include appropriate imaging studies, a systemic workup to rule out MM.